II. Due modelli di filosofia dell’educazione tra apertura e tradizione. Mario Gennari e Francesco Mattei - Cambi, Franco (Studi sulla Formazione/Open Journal of Education, 2014)
The text presents two actual models of philosophy of education. The model of Mario Gennari and the model of Francesco Mattei are organic and critical and can be exemplary in the theoretical and critical pedagogical research.